Circulating Chromogranin A Is Cleaved Into Vasoregulatory Fragments in Patients With Pancreatic Ductal Adenocarcinoma - Reni, Michele; Andreasi, Valentina; Gasparri, Anna Maria; Dugnani, Erica; Colombo, Barbara; Macchini, Marina; Bianco, Mimma; Dallatomasina, Alice; Citro, Antonio; Assi, Emma; Protti, Maria Pia; Esposito, Antonio; et al. (Frontiers in Oncology, 2020)
Chromogranin A (CgA), a secretory protein released in the blood by the neuroendocrine system, consists of a mixture of full-length molecules and fragments endowed of vasoregulatory activity. The extent and the role of CgA fragmentation were investigated in patients with locally advanced or metastatic pancreatic ductal adenocarcinoma (PDAC, n=172). Multivariate analysis showed that full-length CgA was associated with better progression free and overall survival, whereas CgA C-terminal fragmentation was associated with worse prognosis. In vitro studies showed that PDAC cells can promote the cleavage of CgA C-terminal region by activating plasminogen to plasmin. Limited digestion of full-length CgA with plasmin abolished its anti-angiogenic activity and generated pro-angiogenic molecules. The fragmentation of CgA C-terminal region was increased also in murine models of PDAC. In these models, the inhibition of CgA fragmentation with aprotinin, an inhibitor of plasmin and other serine proteases, or the blockade of pro-angiogenic fragments with specific antibodies inhibited the growth of PDAC implanted subcutaneously in mice. Finally, administration of full-length CgA to mice bearing orthotopic PDAC reduced tumor perfusion, as measured by contrast-enhanced ultrasound. These findings suggest that PDAC can promote the cleavage of circulating CgA C-terminal region to generate fragments that regulate the tumor vascular biology and that may represent new potential therapeutic targets.